Penegakan Hukum Pidana Terhadap Anak Pelaku Kejahatan Klitih - Khoerina Azzizah; Beniharmoni Harefa (Jurnal USM Law Review)
This research aims to examine the urgency of providing diversion in criminal law enforcement against juvenile perpetrators of klitih crimes. Klitih, which leads to violence or even murder, can involve a child in legal processes. Involving a child in the criminal justice system can neglect the child's rights in terms of their physical, mental, and social well-being. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System was established to achieve restorative justice and protect the interests of children. The provision of diversion for juvenile offenders is a form of restorative justice. The effective implementation of diversion relies not only on law enforcement agencies but also on the responsibility of parents in supervising and guiding their children who have been involved in criminal activities. The research method used in this study is normative juridical with a legislative approach, supported by comparative approaches and primary, secondary, and tertiary legal sources. The results of this research indicate that the provision of diversion with the return of the child to their parents needs to be emphasized in terms of accountability to prevent tolerance and recurrence of crimes.